Histopathological Spectrum and Risk Stratification of Chronic Inflammatory Dermatoses in Pakistani Population: A Cross-Sectional Study - Ramla Kazmi, Sara Mubeen, Ikram Ul Haq, Aneeq Ahmed Bhatti, Muhammad Naweed Aslam, Masooma Zafar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic inflammatory dermatoses (CIDs), such as psoriasis, lichen planus, chronic eczema, and discoid lupus erythematosus (DLE), are prevalent dermatological conditions marked by immune-mediated inflammation and diverse histopathological patterns. In clinical practice, diagnosis is often based on morphology, while severity assessment lacks uniform histological grading. Objective: To evaluate the histopathological spectrum of CIDs in a Pakistani population and establish a risk stratification model using a cumulative histopathological score (CHS) correlated with clinical severity indices. Methodology: This cross-sectional study was conducted at Sughra Shafi Medical Complex and Services Hospital Lahore from June 2022 to June 2023. A total of n=70 patients with clinically diagnosed CIDs were enrolled. Skin biopsies were evaluated for five parameters: hyperkeratosis/parakeratosis, acanthosis, spongiosis/interface changes, dermal infiltrate, and papillary dermal changes. Each was scored on a scale of 1 to 3. CHS values were used to stratify patients into low (5–8), intermediate (9–11), and high-risk (12–15) categories. Results: Psoriasis was the most common condition (40%), followed by chronic eczema (27.1%), lichen planus (21.4%), and DLE (11.5%). Most psoriasis and eczema patients fell into the intermediate-risk category, while lichen planus and DLE predominantly showed high-risk histology. CHS strongly correlated with clinical indices: PASI (r=0.71), EASI (r=0.65), LPAI (r=0.68), and CLASI (r=0.72). Conclusion: The CHS provides a standardized, reliable method for histological risk stratification in chronic inflammatory dermatoses and correlates significantly with clinical severity. It offers a practical adjunct to guide diagnosis, prognostication, and therapeutic planning in dermatological practice. Keywords: chronic inflammatory dermatoses, histopathology, risk stratification, psoriasis, lichen planus, eczema, discoid lupus erythematosus, Pakistan